Recolonizing native wildlife facilitates exotic plant invasion into Singapore's rain forests - Ho, Chervil (2024)
Halting biological invasions and rewilding extirpated native fauna are conservation interventions to bolster biodiversity, species interactions, and ecosystems. These actions are often considered separately and the potential for reintroduced wildlife to facilitate invasive plants has been largely overlooked. Here, we investigated the role of Singapore's recolonizing native wild pigs (Sus scrofa) in facilitating an invasive weed Miconia crenata into tropical rainforests, which are normally highly resistant to invasion. We conducted line-transect surveys in 11 Singaporean rain forests and used generalized linear mixed models to consider the contribution of pigs' soil disturbances, human forest paths, and other environmental covariates, on the density of M. crenata. We found that M. crenata was more abundant at forest edges and invasion into forest interior was facilitated by pigs, paths, and canopy gaps, but that these effects were all additive, not synergistic (i.e., not multiplicative). These results highlight how modern invasions are driven by multiple disturbances as well as propagule pressure (e.g., urban birds dispersing seeds at forest edges where they establish in pig soil disturbances). Singapore's extensive native forest restoration efforts may have provided plentiful edge and secondary forests that are well suited to pigs and M. crenata, which in turn undermine the aims of fostering later-successional native plant communities. To prevent negative externalities, we suggest that plant restoration and rewilding projects consider the potential role of wildlife in facilitating non-native plants, and couple these actions with preliminary screening of unintended consequences and continued monitoring, as well as limiting human-mediated weed invasion to minimize propagule sources.